A Pilot Study of Inhaled CO Therapy in Neonatal Hypoxia-Ischemia: Carboxyhemoglobin Concentrations and Brain Volumes - Douglas-Escobar, Martha; Mendes, Monique; Rossignol, Candace; Bliznyuk, Nikolay; Faraji, Ariana; Ahmad, Abdullah S.; Doré, Sylvain; Weiss, Michael D. (Frontiers in Pediatrics, 2018)
Objective – The objective of the study was to evaluate the safety of carbon monoxide (CO) as a putative neuroprotective therapy in neonates. Study Design – Neonatal C57BL/6 mice were exposed to CO at a concentration of either 200 or 250ppm for a period of 1 hour. The pups were then sacrificed at 0, 10, 20, 60, 120, 180, and 240 minutes after exposure to either concentration of CO and blood was collected for analysis of carboxyhemoglobin. Following the safety study, 7 day old pups underwent a unilateral carotid ligation. After recovery, the pups were exposed to a humidified gas mixture of 8% oxygen and 92% nitrogen for 20 minutes in a hypoxia chamber. One hour after the hypoxia exposure, the pups were randomized to one of two groups: air (HI+A) or carbon monoxide (HI+CO). An inhaled dose of 250ppm of CO was administered to the pups for 1 hour a day for a period of 3 days. At 7 days post-injury, the pups were sacrificed and the brains analyzed for cortical and hippocampal volumes. Results – CO exposure at 200 and 250ppm produced a peak carboxyhemoglobin of 21.52±1.18 and 27.55 ±3.58%, respectively. The carboxyhemoglobin concentrations decreased rapidly reaching control concentrations by 60 minutes post-exposure. At 14 days of age (7 days post injury), the HI+CO (treated with 1 hour per day of 250ppm of CO for 3 days post-injury) had significant preservation of the ratio ipsilateral/contralateral cortex (median 1.07, 25% 0.97, 75% 1.23, n=10) compared the HI+A group (p<0.05). Conclusion – CO exposure of 250ppm was safe and is effective in preserving cortical volumes following hypoxic-ischemic injury.